A Feasibility study on Golden Pleroma Organic Shop - Ambida, Julie Ann O. (College of Engineering, 2005)
The primary objective of JSP GoldenPlex Trading is the introduction of Golden Pleroma Organic Soap to the local market and to evaluate their proposed expansion in light of available market demand. The soap claims whitening effect on the skin and preventive and curative medicinal properties, among others. It consists of all-natural ingredients such as various fruits and vegetables, coconut virgin oil and other vegetable oils, and is 100% chemical free. It started last April 2005 and is proudly Filipino-made and supports the local farmers by relying solely on indigenous crops. Proceeds from this undertaking sustain several programs under the heading of Zero-Disease, Zero-Waste and Zero-Crime by a collaboration of non-government organizations and church organizations and ministries. Golden Pleroma is currently a background operation with purely manual equipment and has only produced and sold 3000 units so far. However, user feedback is very promising and repeat orders are frequent. In line with the objective of penetrating the local market, a feasibility study of the marketing, technical and financial analysis of this venture was conducted. The local soap market is analyzed and a supply-demand gap established with the intention of capturing the unsatisfied demand. Survey results, which totaled 200 respondents, are analyzed in relation to customer preferences in body soaps and market share data is also estimated from it. The market is then segmented according to location, population characteristics, attitudes and lifestyle, and behavior. Individuals geared toward a more healthful whose income range is P 30,000 and above lifestyle are identified as the target market and the product is positioned as a local organic soap that's cheaper relative to imported organic brands, possessing most of the soap preferences of the majority of the population and offers a host of benefits commonly not found in just one product. With regard to the manufacturing aspect or the technical feasibility of mass producing the Golden Pleroma Organic Soap, the specific production processes, raw materials, required equipment and the general facility requirements were determined and the available options and alternatives were studied. An analysis of the financial viability of the project was also undertaken with pro-forma balance sheets, income statements and cash flow statements corresponding to the planning horizon of five years were presented. Financial rations were also studies and the financial position of the venture projected and analyzed. Lastly, the social profitability of the project is considered through an evaluation of the economic and social benefits of Golden Pleroma Organic Soap to the local community. The project feasibility study has found Golden Pleroma Organic Soap to be feasible in all aspects and a profitable business venture.